From a design museum towards a european cultural place: a design milieu strategies for the european design culture in the globalization era - Gonzaga, Susana (2017)
The aim of this thesis is to establish the strategic lines for the creation of a place dedicated to European Design. Based on the survey and study of European Design museums, and by analyzing their typologies, missions, relationships with local and audience, we verified that the European museology trend focuses mainly on the conservation and communication of industrial production artifacts mostly of nationalistic nature, with little differentiation from its peers, be it in the available services, be it in museum strategies. Based on the theoretical-critical background of the design culture and of the Museum Studies, we have associated the evolution of the subject to: the globalization of the creation and production processes; new cultural ways and expressions; and the European Union’s strategies for the creation of transcultural environments. By crossing these macro-areas with the results obtained in the mapping of the design museums we were able to formulate the following hypothesis: are the places dedicated to design communicating its diversity, plurality and multiplicity of expressions in the contemporary European society? From this hypothesis comes the research question that guided this investigation. How can we build a systemic and holistic vision of the European design culture, through its exhibition places and relationship with its audience? To compose this plan, design museums, as well as Design Week/Festival events and Design Districts were specified as the main agents in the conservation, dissemination, exhibition and divulgation of design in Europe. By resorting to a qualitative methodology to analyze each of these agents, and to the Ground Theory instruments, we were able to, on one hand; determine the diachronic portrait of this cultural system, and on the other, to obtain the results of its social and cultural impact. The contrast of these results has given us empirical evidence that provides a project opportunity. Thus appears the Design Milieu concept. It is a place that spotlights the plurality of the European project practice and compares it to itself and the world. It is a place that gathers a museum’s curatorial and tutorial features; with the cultural, interventional, performing and contemporary character of an event; and with close relationships with the community (public and professional) embedded in the urban territory, as a district.